Difference between Cutting Surface of Al Foam and Solid Al Machined by WEDM Technology - Špalek, František; Sadílek, Marek; Čep, Robert; Petrů, Jana; Kratochvíl, Jiří; Čegan, Tomáš (Manufacturing Technology Journal, 2017)
The article deals with a comparison of machining of two chemically very similar materials of aluminium alloy, however, with various internal structures by means of non-conventional machining technology of electro-erosive wire cutting (WEDM). The first material used was a right parallelepiped of ALPORAS aluminium foam with porous structure produced by a method of powder metallurgy. As the second material designed to the comparison EN AW 5005 alloy was chosen owing to high aluminium content and therefore a very near chemical composition of the compared material. The samples with circular section of identical height and nominal diameter were produced. On the tested materials sizes of the cutting width were tested, surface structures after machining were observed, dimensional accuracy of cut samples were evaluated and time relationship between cutting of compact and porous structures of aluminium alloy were defined by means of a microscope.
Keywords: aluminium alloy; WEDM; non-conventional technology; measurement